Fiscal incentives and corporate financing - a flow of funds analysis 1964-1982 - Stewart, J. C. (Statistical and Social Inquiry Society of Ireland, 1986)
This paper examines flows of funds for Irish public companies for the period 1964-1982 with particular reference to the effects of fiscal incentives. The study uses published accounts of companies as a data source. Sources of finances were found to vary cyclically, as was the change in cash balances and stocks. The paper demonstrates the low level of corporate saving, in particular, if an allowance is made for stock appreciation. Since 1973 aggregate dividend payments are seen to be higher than aggregate tax payments. The paper shows that the main source of external finance is from the commercial banks. The paper also notes a switch from short-term bank borrowing to long-term borrowing. The Stock Exchange/shareholders accounted for a low proportion of external finance although the proportion is higher than that found for public companies in the UK for some years. Finally a weak though positive relationship was found between the export/sales ratio and reliance on share issues (preference and equity). The paper concludes that the allocation of funds in Ireland can be best described as a private bureaucratic allocation of funds in contrast to a capital market based financial system such as the US or a system of State allocation as in the case of France and this raises certain issues relating to the efficiency of this allocation. This paper begins with a description of the study population. Secondly there is a brief discussion of some of the problems of preparing flows of funds from the accounts of individual firms. Thirdly the overall importance of different sources of funds is examined, and some effects of fiscal incentives on corporate financing are considered. Finally some conclusions and policy implications are discussed.
Read before the Society, 27 February 1986
Keywords: Fund analysis; Fiscal incentive; Corporate funds; 314.15